Brief Review of the Role of Glycogen Synthase Kinase-3β in Amyotrophic Lateral Sclerosis - Seong-Ho Koh; Wonki Baek; Seung H. Kim (Neurology Research International)
Glycogen synthase kinase-3β (GSK-3β) is known to affect a diverse range of biological functions controlling gene expression, cellular architecture, and apoptosis. GSK-3β has recently been identified as one of the important pathogenic mechanisms in motor neuronal death related to amyotrophic lateral sclerosis (ALS). Therefore, the development of methods to control GSK-3β could be helpful in postponing the symptom progression of ALS. Here we discuss the known roles of GSK-3β in motor neuronal cell death in ALS and the possibility of employing GSK-3β modulators as a new therapeutic strategy.